PTH-097 Defining Patient-Centred Professionalism in Gastroenterology. (4th June 2013) - Wright, S; Williams, J G; Hutchings, H A; Rapport, F
Abstract : Introduction: The UK IBD audit 3 rd round (RCP, 2011)shows that there has been sustained improvement in patient-centred care in terms of clinician commitment to improved quality of care and the provision of specialist IBD nursing and patient education for patients with IBD. This study explores the meaning of the concept 'patient-centred professionalism' in gastroenterology. The objectives of this study are: To clarify the meaning of patient-centred professionalism in terms of how it relates to professional practise and patient-professional interaction in gastroenterological outpatient clinic consultations To define the concept according to the views and experiences of healthcare professionals, stakeholders and IBD patients. To create materials which may support and enhance optimal professional practise in outpatient clinics for patients with IBD Methods: A qualitative study using observation and semi-structured interviews. Ethnographic observation was conducted in 8 outpatient clinics from within one local health board (Abertawe Bro Morgannwg University Health Board). Clinics were led by consultant physician gastroenterologists; surgeons, specialist nurses and joint colorectal MDT clinics. A total of 31 consultations were observed with IBD patients aged between 18–70 years old. A total of 40 in-depth qualitative interviews were conducted with IBD patients; healthcare professionals and eminent stakeholders in gastroenterology. Ethnographic fieldnotes from observation and transcripts from interviews were analysed using a thematic analysis approach. Results: Key characteristics of patient-centred professionalism in gastroenterology have been elicited and categorised into thematic areas including shared decision making; transparency, openness and honesty; information and knowledge transfer and integrated approaches to care. Patients' descriptions of experiences of consultations with healthcare professionals are vivid and reveal both best practise in gastroenterological practises in secondary care as well as unexpected views about encounters with the medical profession. An output from this study involves the creation of materials to support gastroenterological outpatient clinic consultations to enhance the optimal professional practise and patient-professional communication. Conclusion: Patients' understandings of patient-centred professionalism, coupled with healthcare professionals and stakeholder understandings of the concept, offer the opportunity to develop enhanced consultations in gastroenterological outpatient clinics. Disclosure of Interest: None Declared. Reference: The UK IBD Audit 3rd Round. The UK IBD Audit Steering Group, May 2011. RCP